Biomechanical Analysis of Instability in Rotational Distal Fibula Fractures (OTA/AO 44-B1) With an Intact Deltoid Ligament. Issue 8 (August 2019) - Hempen, Eric; Butler, Bennet; Barbosa, Mauricio; Muriuki, Muturi; Havey, Robert; Kadakia, Anish
Abstract : Objectives: To biomechanically analyze instability in supination external rotation (SER) II/III patterns. Methods: Nineteen cadaver legs were tested in a mechanical jig. One, 2, 3, and 4 Nm of external rotation were applied to intact ankles, SER II injuries, and SER III injuries. The talar position relative to the tibia was recorded using 3D motion tracking. Change from the unloaded state in each condition and the torque level was calculated. Results were analyzed using analysis of variance with post hoc paired t tests. Results: SER II showed statistically significant differences from the intact state with coronal translation (2, 3, and 4 Nm), sagittal translation (1 and 2 Nm), axial rotation (1, 2, 3, and 4 Nm), and coronal rotation (3 and 4 Nm). SER III showed statistically significant differences from the intact state with coronal translation (2, 3, and 4 Nm), sagittal translation (1, 2, and 3 Nm), axial rotation (1, 2, 3, and 4 Nm), and coronal rotation (3 and 4 Nm). SER II and SER III differed significantly from each other with coronal translation (1, 2, and 3 Nm), axial rotation (2, 3, and 4 Nm), and coronal rotation (1, 3, and 4 Nm). Conclusion: Instability in SER injuries has only been described with coronal translation and suggests that deltoid rupture is necessary. Our data demonstrate instability in SER II/III in sagittal translation and axial rotation as well as subtle instability in coronal translation. The clinical impact is unclear, but better understanding of long-term sequelae of this instability is needed.